Pengaruh Kemudahan dan Keamanan Terhadap Purchase Intention Dimediasi Kepercayaan Pada Pengguna Shopee Paylater - Laura Ayu Selvianita; Muhammad Ridwan Basalamah; Restu Millaningtyas (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study aims to examine the influence of perceived ease of use and security on purchase intention, with trust serving as a mediating variable among Shopee Paylater users. The research adopts a quantitative approach and employs the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method to test relationships among variables specified in the research model. The data used are primary data collected through structured questionnaires distributed to respondents. The population of this study consists of students from the Faculty of Economics and Business at Universitas Islam Malang. The sampling technique applied is non-probability sampling using a purposive sampling method, involving 120 respondents with prior experience using Shopee Paylater in online transactions. The findings indicate that perceived ease of use does not have a significant direct effect on purchase intention. In contrast, security has a significant effect on purchase intention. Moreover, perceived ease of use and security significantly influence user trust. Trust also significantly affects purchase intention. Furthermore, perceived ease of use and security have a significant indirect effect on purchase intention through trust as a mediating variable. These results suggest that trust plays an important role in mediating the effects of ease of use and security on users’ purchase intention toward Shopee Paylater. Keywords: Perceived Ease of Use, Security, Trust, Purchase Intention